Selective Interaction of Colistin with Lipid Model Membranes - Dupuy, Fernando Gabriel (2018)
Although colistin's clinical use is limited due to its nephrotoxicity, colistin is considered to be an antibiotic of last resort because it is used to treat patients infected with multidrug-resistant bacteria. In an effort to provide molecular details about colistin's ability to kill Gram-negative (G(−)) but not Gram-positive (G(+)) bacteria, we investigated the biophysics of the interaction between colistin and lipid mixtures mimicking the cytoplasmic membrane of G(+), G(−) bacteria as well as eukaryotic cells. Two different models of the G(−) outer membrane (OM) were assayed: lipid A with two deoxy-manno-octulosonyl sugar residues, and Escherichia coli lipopolysaccharide mixed with dilaurylphosphatidylglycerol. We used circular dichroism and x-ray diffuse scattering at low and wide angle in stacked multilayered samples, and neutron reflectivity of single, tethered bilayers mixed with colistin. We found no differences in secondary structure when colistin was bound to G(−) versus G(+) membrane mimics, ruling out a protein conformational change as the cause of this difference. However, bending modulus KC perturbation was quite irregular for the G(−) inner membrane, where colistin produced a softening of the membranes at an intermediate lipid/peptide molar ratio but stiffening at lower and higher peptide concentrations, whereas in G(+) and eukaryotic mimics there was only a slight softening. Acyl chain order in G(−) was perturbed similarly to KC. In G(+), there was only a slight softening and disordering effect, whereas in OM mimics, there was a slight stiffening and ordering of both membranes with increasing colistin. X-ray and neutron reflectivity structural results reveal colistin partitions deepest to reach the hydrocarbon interior in G(−) membranes, but remains in the headgroup region in G(+), OM, and eukaryotic mimics. It is possible that domain formation is responsible for the erratic response of G(−) inner membranes to colistin and for its deeper penetration, which could increase membrane permeability.